Analysis of voltage sag propagation through the distribution network - Klaić, Zvonimir (JET on-line, 2014)
Power quality is a hugely important aspect of power delivery. This paper dealswith voltage sags, which are reflected in the aspect of power quality. During a voltage sag, the voltage at the customer terminal is reduced and can cause undesirable equipment trips. The main causes of voltage sags are short-circuit faults. Most short-circuits in a power system are either single line-to-ground or two phase short circuits. The causes of voltage sags in the power system are not the subject of this paper. This paper analyses the propagation of single-phase voltage sags caused by a line-to-ground short circuit in a transmission network, from the high voltage level to the distribution level through various types of transformers. The influence of the transformer winding connection on the propagation of voltage sag is investigated from the theoretical aspect, the practical aspect and the computer simulation aspect. One example of voltage sag propagation from the transmission network to the distribution network that is captured with the power quality measurements is analysed. Theoretical calculations of voltage sag propagation through the various types of transformer windings connections are presented and compared to the measurement result. Furthermore, a computer model of the observed distribution network is modelled in DigSILENT Power Factory software. This model is used for the simulation of voltage sag propagation. The results of the computer simulation are presented and comparedto the measurements. Conclusions and comments on the results are presented at the end of the paper.
Keywords: computer simulation; električna energija; power quality; simulacija; transformatorsko navitje; transformer winding; upad napetosti; voltage sag